Annual International Conference on Social Sciences and Humanities (AICOSH 2020) 2020
DOI: 10.2991/assehr.k.200728.040
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness, Hope, and Satisfaction With Life Among Senior High School Students Viewed From Family-related Characteristics in Indonesia

Abstract: This study aims to determine the differences in forgiveness, hope, and satisfaction with life based on familyrelated characteristics, namely birth order, the total number of siblings, parents' marriage status, housemate, parents' age category, parents' occupation nature, and parents' education, aside from general demographic characteristics, among Indonesian senior high school age students. Participants in this study were 909 students of a vocational high school in Semarang, Indonesia obtained through cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
1
Order By: Relevance
“…Those typical results relate to differences in trend of correlations with hope and life satisfaction, that may be explained by the characteristics of hope, as well as life satisfaction, as found among adolescents. In this study, unlike life satisfaction which is more likely to be normally distributed, the numbers in each category of hope increase with the score (supported by [11]). Previous findings in the population of teenagers explained how the presence of adolescent egocentrism (David Elkind's Theory) in the form of personal fable can result in bias optimism [24] which then seems to be related to hope [37].…”
Section: Correlations Among Variables According To Anxiety Levels Sex and Both Anxiety Levels And Sexmentioning
confidence: 50%
See 2 more Smart Citations
“…Those typical results relate to differences in trend of correlations with hope and life satisfaction, that may be explained by the characteristics of hope, as well as life satisfaction, as found among adolescents. In this study, unlike life satisfaction which is more likely to be normally distributed, the numbers in each category of hope increase with the score (supported by [11]). Previous findings in the population of teenagers explained how the presence of adolescent egocentrism (David Elkind's Theory) in the form of personal fable can result in bias optimism [24] which then seems to be related to hope [37].…”
Section: Correlations Among Variables According To Anxiety Levels Sex and Both Anxiety Levels And Sexmentioning
confidence: 50%
“…Previous research has shown that incomplete family structures that require adolescents to live with other relatives or other people, or even live alone have the lowest level of forgiveness, hope, and life satisfaction; on the other hand, those who live with both parents have the highest level. Meanwhile, those who live with one parent have a level in between [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain dari sisi budaya, alat ukur SWLS juga cocok digunakan dari berbagai kalangan, di Indonesia SWLS dilakukan penelitian kepada siswa SMA (Rahmandani & Kahija, 2020), mahasiswa di perguruan tinggi (Waskito dkk., 2018), guru di sekolah swasta (Novanto & Pali, 2019), dan dosen di salah satu perguruan tinggi di Indonesia (Novanto dkk., 2020), bahkan sampai lansia yang tinggal di panti jompo (Roswiyani dkk., 2020).…”
Section: Pendahuluanunclassified